Uterine artery embolization or myomectomy for women with uterine fibroids: Four-year follow-up of a randomised controlled trial. (January 2022) - Daniels, Jane; Middleton, Lee J.; Cheed, Versha; McKinnon, William; Sirkeci, Fusun; Manyonda, Isaac; Belli, Anna-Maria; Lumsden, Mary Ann; Moss, Jonathan; Wu, Olivia; McPherson, Klim; on behalf of the FEMME Trial Collaborative Group,
Abstract: Objective: To examine the quality of life experienced by women with symptomatic uterine fibroids who had been treated with UAE in comparison to myomectomy. We report the four-year follow-up of the FEMME randomised trial. Two-year follow-up data has been previously reported. Study Design: Premenopausal women who had symptomatic uterine fibroids amenable to myomectomy or uterine artery embolization were recruited from 29 UK hospitals. Women were excluded if they had significant adenomyosis, any malignancy, pelvic inflammatory disease or had had a previous open myomectomy or uterine artery embolization. Participants were randomised to myomectomy or embolization in a 1:1 ratio using a minimisation algorithm. Myomectomy could be open abdominal, laparoscopic or hysteroscopic, according to clinician preference. Embolization of the uterine arteries was performed according to local practice, under fluoroscopic guidance. The primary outcome measure was the Uterine Fibroid Symptom Quality of Life questionnaire, adjusted for baseline score and reported here at four years post-randomisation. Subsequent procedures for fibroids, pregnancy and outcome were amongst secondary outcomes. Trial registration ISRCTN70772394 https://doi.org/10.1186/ISRCTN70772394 Results: 254 women were randomized, 127 to myomectomy (105 underwent myomectomy) and 127 to uterine artery embolization (98 underwent embolization). At four years, 67 (53%) and 81 (64%) completed UFS-QoL quality of life scores. Mean difference in the UFS-QoL at 4 years was 5.0 points (95% CI −1.4 to 11.5; p = 0.13) in favour of myomectomy. There were 15 pregnancies in the UAE group and 7 in the myomectomy group, with a cumulative pregnancy rate to four years of 15% and 6% respectively (hazard ratio: 0.48; 95% CI 0.18–1.28). The cumulative repeat procedure rate to four years was 24% in the UAE group and 13% in the myomectomy group (hazard ratio: 0.53; 95% CI 0.27–1.05). Conclusions: Myomectomy resulted in greater improvement in quality of life compared with uterine artery embolization, although by four years, this difference was not statistically significant. Missing data may limit the generalisability of this result. The numbers of women becoming pregnant were too small draw a conclusion on the effect of the procedures on fertility.